THE ROLE OF PRINCIPLES OF DESIGN IN THE AESTHETICS OF LINEAR FORMATIONS IN THE KISWAH OF KAABA - Alashari, Duaa Mohammed (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2023)
The linear formations in the Kaaba's covering are characterized by several design principles that have effectively contributed to giving the Holy Kaaba's covering an aesthetic appearance. Therefore, this study aims to reveal the technical design foundations of the covering of the Kaaba, according to a methodological and analytical perspective. The method used in this study is the descriptive-analytical method. This study is classified under applied field studies. The study concluded that the linear formations present in the covering of the Holy Kaaba enjoy several design foundations of an artistic and aesthetic nature. These foundations are balance, supremacy, rhythm, unity, contrast, coordination, proportionality, symmetry, and sequence. The study also concluded that artistic design principles had been applied to the highest degree to achieve the aesthetic goal of designing the linear formations in the cladding and to enhance the artistic dimensions through a functional and aesthetic rhythm.